THE PREPAREDNESS OF PRE-SERVICE TEACHERS ON THE REQUIRED PROGRAMS TO MEET STANDARDS: Received: 14th May 2021; Revised: 14th August 2021, 25th September 2021, 24th January 2022; Accepted: 30th January 2022 - Bihasa, Donnabel B (PUPIL: International Journal of Teaching, Education and Learning, 2022)
“A quality education begins with the best teachers”, Pyne, 2014. Capacitating the teaching force helps in the improvement of learners’ performance. Attracting the best educators in the profession, where respect, nobility, and prestige were sustained by exhibiting quality teaching to produce the best output or performance and an untiring motivation for student's learning will have a positive impact. As an educator let us live by this famous quote, “Teaching is the noblest profession” and uphold its meaning by being a model to our learners. This qualitative study which involved three participants tried to scrutinize the preparedness of the PSTs on the required teacher preparation programs to meet standards offered by the Department and use descriptive narrative to treat the gathered data. It also explored the practices of the TEIs in preparation for the challenges of the pre-service teachers when they are already in the school. The results of this study stated that there is already familiarity among the pre-service teachers on the existing programs offered by the department for the professional learning and development of in-service teachers. And the pre-service teachers planned to engage and participate in continuing education, school learning action cells, in-service training, seminars, and workshops for upskilling and reskilling and for professional development.